Comparison of Different Phenotypic Approaches To Screen and Detect mecC-Harboring Methicillin-Resistant Staphylococcus aureus - Kriegeskorte, André (J Clin Microbiol, 2017)
Similar to mecA, mecC confers resistance against beta-lactams, leading to the phenotype of methicillin-resistant Staphylococcus aureus (MRSA). However, mecC-harboring MRSA strains pose special difficulties in their detection. The aim of this study was to assess and compare different phenotypic systems for screening, identification, and susceptibility testing of mecC-positive MRSA isolates. A well-characterized collection of mecC-positive S. aureus isolates (n = 111) was used for evaluation. Routinely used approaches were studied to determine their suitability to correctly identify mecC-harboring MRSA, including three (semi)automated antimicrobial susceptibility testing (AST) systems and five selective chromogenic agar plates. Additionally, a cefoxitin disk diffusion test and an oxacillin broth microdilution assay were examined. All mecC-harboring MRSA isolates were able to grow on all chromogenic MRSA screening plates tested. Detection of these isolates in AST systems based on cefoxitin and/or oxacillin testing yielded overall positive agreements with the mecC genotype of 97.3% (MicroScan WalkAway; Siemens), 91.9% (Vitek 2; bioMérieux), and 64.9% (Phoenix, BD). The phenotypic resistance pattern most frequently observed by AST devices was “cefoxitin resistance/oxacillin susceptibility,” ranging from 54.1% (Phoenix) and 83.8% (Vitek 2) to 92.8% (WalkAway). The cefoxitin disk diffusion and oxacillin broth microdilution assays categorized 100% and 61.3% of isolates to be MRSA, respectively. The chromogenic media tested confirmed their suitability to reliably screen for mecC-harboring MRSA. The AST systems showed false-negative results with varying numbers, misidentifying mecC-harboring MRSA as methicillin-susceptible S. aureus. This study underlines cefoxitin's status as the superior surrogate mecC-positive MRSA marker.